190k views
1 vote
h(x) = 17+x/6h(-18) I know some stuff about function but this one i need someone to explain it step by step

User Inertiatic
by
6.0k points

1 Answer

1 vote

Answer

h(-18) = 14

Step-by-step explanation

We are asked to evaluate h(-18) given that


h(x)=17+(x)/(6)

h(-18) will be substituting for x in the given function for h(x).


\begin{gathered} h(-18)=17+(-18)/(6) \\ =17+(-3) \\ =17-3 \\ =14 \end{gathered}

Hence, h(-18) = 14

Hope this Helps!!!

User Roshith
by
6.2k points